Gendered Impact of Climate-Induced Migration: Enhancing Resilience and Socio-Economic Reintegration for Women in Punjab, Pakistan - Muhammad Usman Arshad, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This research investigates the gendered dimensions of climate-induced migration in Punjab, Pakistan, focusing on the resilience and socio-economic reintegration of women. Punjab, a region frequently affected by extreme climate events such as floods and droughts, witnesses significant migration flows that disproportionately impact women due to existing socio-cultural norms and systemic inequities. The study employs a mixed-methods approach, combining qualitative interviews with affected women and quantitative analysis of migration patterns and socio-economic outcomes. Key findings reveal that women experience heightened challenges, including loss of livelihoods, limited access to resources, and social stigmatization during and after migration. However, they also exhibit remarkable resilience, leveraging social networks, traditional skills, and adaptive strategies to navigate adversity. This paper underscores the need for gender-sensitive policies to enhance resilience and facilitate the socio-economic reintegration of women. It advocates for targeted interventions, such as vocational training, access to microfinance, and inclusive community development programs, to empower women and promote equitable recovery. By addressing structural barriers and fostering gender equity, this research aims to inform policymaking and contribute to sustainable solutions for climate-induced migration in Pakistan.